2013
DOI: 10.1007/s13238-013-3079-9
|View full text |Cite
|
Sign up to set email alerts
|

Developing controllable hypermutable Clostridium cells through manipulating its methyl-directed mismatch repair system

Abstract: Development of controllable hypermutable cells can greatly benefit understanding and harnessing microbial evolution. However, there have not been any similar systems developed for Clostridium, an important bacterial genus. Here we report a novel two-step strategy for developing controllable hypermutable cells of Clostridium acetobutylicum, an important and representative industrial strain. Firstly, the mutS/L operon essential for methyldirected mismatch repair (MMR) activity was inactivated from the genome of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 44 publications
0
7
1
Order By: Relevance
“…While both the wt and ΔmutS-adapted strains (AE and MAE, respectively) each evolved to grow significantly better than unadapted wt cells at low pH, genome resequencing of the mutants confirmed that mutS inactivation decreased DNA replication fidelity and yielded derivatives with a greater number of genetic changes (Table S2 and S3). Previous studies investigating the effect of inactive MMR on the mutation rate have shown increased mutation rates of 10-to 1,000-fold (12,13,23,24). Our observed 3.3-fold increase in the number of mutations in L. casei 12A-MAE is lower than the rates previously reported.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…While both the wt and ΔmutS-adapted strains (AE and MAE, respectively) each evolved to grow significantly better than unadapted wt cells at low pH, genome resequencing of the mutants confirmed that mutS inactivation decreased DNA replication fidelity and yielded derivatives with a greater number of genetic changes (Table S2 and S3). Previous studies investigating the effect of inactive MMR on the mutation rate have shown increased mutation rates of 10-to 1,000-fold (12,13,23,24). Our observed 3.3-fold increase in the number of mutations in L. casei 12A-MAE is lower than the rates previously reported.…”
Section: Discussioncontrasting
confidence: 82%
“…Under stressed conditions, hypermutability can be leveraged to increase an organism's fitness and achieve a desired phenotype through adaptive laboratory evolution (1-3). High mutation rates resulting from a deficient MMR process have been previously shown to increase the fitness of an organism in defined environments (13,23). In this study, we explored the potential for coupling transient inactivation of the MMR process with adaptive evolution to obtain L. casei strains with increased lactic acid resistance at low pH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that in microbial cells, elevated mutation rates can be exploited to facilitate ALE toward better fitness compared with non-mutator cells (Sniegowski et al, 1997; Giraud et al, 2001a; Notley-McRobb et al, 2002; Barrick et al, 2009; LaCroix et al, 2015). Often, MMR-impaired cells have been used as the mutator strain in numbers of ALE applications (Luan et al, 2013; Overbeck et al, 2017; Wannier et al, 2018) because MMR-inactivation were known to generate moderate mutators in E. coli (Taddei et al, 1997; Rosche and Foster, 1999; Tenaillon et al, 1999; Loh et al, 2010; Sprouffske et al, 2018). In laboratory settings, the desired ALE results can be achieved when strains become best-adapted for survival in an unfavorable condition.…”
Section: Discussionmentioning
confidence: 99%
“…So by placing mutS and/or mutL under the control of inducible promoters as well it may be possible to extend the range of tunable mutation rates downward; ( Foster 1999 ) found that overexpression of mutS, mutL, or both reduced the number of reversion mutations of the lac or tet alleles. ( Luan et al 2013a ) adjusted the mutation rate of Clostridium acetobutylicum by altering mutS and mutL levels, and did not attain lower than wildtype mutation rates.…”
Section: Discussionmentioning
confidence: 99%